If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 2) + (3y + -13) = 90 Reorder the terms: (2 + 2y) + (3y + -13) = 90 Remove parenthesis around (2 + 2y) 2 + 2y + (3y + -13) = 90 Reorder the terms: 2 + 2y + (-13 + 3y) = 90 Remove parenthesis around (-13 + 3y) 2 + 2y + -13 + 3y = 90 Reorder the terms: 2 + -13 + 2y + 3y = 90 Combine like terms: 2 + -13 = -11 -11 + 2y + 3y = 90 Combine like terms: 2y + 3y = 5y -11 + 5y = 90 Solving -11 + 5y = 90 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 5y = 90 + 11 Combine like terms: -11 + 11 = 0 0 + 5y = 90 + 11 5y = 90 + 11 Combine like terms: 90 + 11 = 101 5y = 101 Divide each side by '5'. y = 20.2 Simplifying y = 20.2
| 3/4*2/7 | | 5(3-x)=4(x-3) | | (3z+5)+(7z-5)+90=180 | | 7+4(2+3x)=-15 | | 90-4x=15x-5 | | 5n+5.23=109.73 | | 5y-2+8y=31 | | (3z+1)+(2z-6)+90=180 | | 7(a-8)+33=3(a-5) | | 20=y-9 | | 7x+3-5x+8+4x-1= | | z+8=-20 | | (3z+1)+(2z-6)=180 | | N/9+10.36=25.36 | | 6(x-3)=4(x-4)+2(x-1) | | N/6+3=12 | | 2X^2+5X=2X+9 | | 6(x+5)=7x+30 | | 8x+37=8x+13 | | (6z-12)+(5z+16)=180 | | z^2+4z+4+2i=0 | | 1+3(x-5)=7+x | | 0.6a=6 | | (6z-12)+(5z+16)=90 | | 7(x+7)=8x+40 | | 7x+3-5x+84x-1= | | 0.625=0.5r | | (6z+12)+(5z+16)=90 | | N^2-4N-5=0 | | W-4.58=1.78 | | 3/4(t-2)-2/5(2t-3)=3/5 | | 10x-4=8x+1 |